Co-pyrolysis of rice straw and polypropylene using fixed-bed pyrolyzer - Izzatie, N.I. (Institute of Physics Publishing, 2016)
The present work encompasses the impact of temperature (450, 500, 550, 600 °C) on the properties of pyrolysis oil and on other product yield for the co-pyrolysis of Polypropylene (PP) plastics and rice straw. Co-pyrolysis of PP plastic and rice straw were conducted in a fixed-bed drop type pyrolyzer under an inert condition to attain maximum oil yield. Physically, the pyrolysis oil is dark-brown in colour with free flowing and has a strong acrid smell. Copyrolysis between these typically obtained in maximum pyrolysis oil yields up to 69 by ratio 1:1 at a maximum temperature of 550 °C. From the maximum yield of pyrolysis oil, characterization of pyrolysis product and effect of biomass type of the composition were evaluated. Pyrolysis oil contains a high water content of 66.137 wt.. Furfural, 2- methylnaphthalene, tetrahydrofuran (THF), toluene and acetaldehyde were the major organic compounds found in pyrolysis oil of rice straw mixed with PP. Bio-char collected from co-pyrolysis of rice straw mixed with PP plastic has high calorific value of 21.190 kJ/g and also carbon content with 59.02 wt. and could contribute to high heating value. The non-condensable gases consist of hydrogen, carbon monoxide, and methane as the major gas components. © Published under licence by IOP Publishing Ltd.